Print media Donbas in 1923-1924 years - Elmira Aliyeva (Cхід, 2013)
This article attempts to detail and thoroughly analyze the development of print media Donbas during the new economic policy, keeping the thought that the press was and remain a powerful influence weighed on the formation of public opinion research that requires special attention of historians. The article characterized by quantitative, qualitative composition of printed periodicals in the region, the main activities of the central government on the press and especially the implementation of the city.